Petrografia e Microscopia Eletrônica de Varredura de Diferentes Gerações de Peleodunas Eólicas Quaternárias do Morro de Santa Maria, Município de Laguna, SC. - MARTINHO, CAROLINE THAÍS; GIANNINI, PAULO CÉSAR FONSECA (Pesquisas em Geociências, 2001)
Four stratigraphic units of Quaternary sands, interpreted as generations of eolian deposits, are recognized in the Santa Catarina mid-south coast (generations 1, 2, 3 and 4). In previous studies, the distinction of these units with base in grain-size and heavy minerals data presented limitations. In this paper, the units 1, 2 and 3, outcropping in the Santa Maria hill (to south from Laguna town), were compared by petrographic and SEM-EDS analyses, what made possible a better characterization and differentiation among these units. These analyses evidenced differences as for the cement texture and to the abundance of predominantly intraclastic lithic components. In general, the units of studied paleodunes are composed by quartzous sands, cemented by caulinitic-organic-ferruginous material. In the unit 1 the cementation degree is higher, the cement possesses colloidal precipitate aspect and meniscus texture. The higher mineralogical maturity and lower textural maturity of this unit are coherent whit the supposition of older depositional age. The unit 2, supposedly younger, has lower cementation degree, higher textural maturity and lower mineralogical maturity. It could be, partly, product of the reworking of older eolian generations. The existence of glauconite clasts in the two older generations (units 1 and 2) would attest the influence of coastal sedimentary supply to the eolian deposits. The unit 3 is inconsolidated, with only a fine cement coating involving the grains, what confirms its character of younger generation.